2018
DOI: 10.1093/zoolinnean/zlx109
|View full text |Cite
|
Sign up to set email alerts
|

Kinetid structure in sponge choanocytes of Spongillida in the light of evolutionary relationships within Demospongiae

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…The choanocyte kinetids of Oscarella lobularis and O. balibaloi closely resemble the kinetids of previously studied sponge species (Pozdnyakov, & Karpov, 2013, 2016a, 2016bPozdnyakov et al, 2017;Pozdnyakov, Sokolova, Ereskovsky, & Karpov, 2018). Their choanocytes have apical nuclei connected to the kinetosomes with fibrillar roots.…”
Section: Discussionsupporting
confidence: 71%
“…The choanocyte kinetids of Oscarella lobularis and O. balibaloi closely resemble the kinetids of previously studied sponge species (Pozdnyakov, & Karpov, 2013, 2016a, 2016bPozdnyakov et al, 2017;Pozdnyakov, Sokolova, Ereskovsky, & Karpov, 2018). Their choanocytes have apical nuclei connected to the kinetosomes with fibrillar roots.…”
Section: Discussionsupporting
confidence: 71%
“…There are, however, some basic differences between sponges and choanoflagellates in how their collar and flagella interact, suggesting that choanocyte/choanoflagellate similarity might be superficial and that specific homology cannot be automatically assumed (see [71] for details). Indeed, recent ultrastructural studies on sponge choanocytes and choanoflagellates show that they are fundamentally different in many respects (see [72][73][74] for details), some of which are among the very few ultrastructural systems in eukaryotic cells considered sufficiently conservative to indicate phylogenetic relationships [75][76][77]. For example, specific features of the flagellar apparatus of the sponge Ephydatia fluviatilis are more similar to zoospores of chytrids than to choanoflagellates [78].…”
Section: Origins Of Multicellularitymentioning
confidence: 99%
“…Another important source of information for phylogenies is the organization of the kinetids (flagellar apparatus). It has been suggested that the ultrastructure of the kinetids is useful for the phylogeny of Porifera (Pozdnyakov & Karpov, ; Pozdnyakov, Sokolova, Ereskovsky, & Karpov, , ). Conversely, we now believe that the general organization and architecture of the aquiferous system observed in previous investigations and in this work (summarized in Table ) do not corroborate the idea that these characteristics are useful to understand/construct the phylogeny of Haplosclerida.…”
Section: Discussionmentioning
confidence: 99%